High Prevalence of Parvovirus B19 IgG Antibody among Hemophilia Patients in Center for Special Diseases, Shiraz, Iran - M Mahmoodian Shooshtari; M Nabi Foroghi; R Hamkar (Tehran University of Medical Sciences, 2005)
Human parvovirus B19, the causative agent of fifth disease in childhood, is non-enveloped DNA virus and resistant to many physicochemical agents. B19 is a potential risk to hemophiliac patients receiving blood products. To determine the prevalence of the corresponding antibody in patients with hemophilia A or B or Von Will brand's disease (VWBD), we tested 180 hemophilia patients aged 1-45 years for anti B19 IgG. This work was descriptive, cross-sectional study. The results were compared with those of 400 age-matched controls, male blood donors and male children (18-45 and 3-17 years of age, respectively). The overall prevalence of B19 IgG in the hemophilia patients was 74% (133/180), and in the controls 56.5% (226/400, P